The Muppet show. Season three [videorecording (DVD)] - Oz, Frank; Henson, Jim (Distributed by Buena Vista Home Entertainment, 2008)
Join the hardest working Muppets in showbiz-- Kermit the Frog, Miss Piggy, Animal and Fozzie Bear in this fall-down-funny third season.